Banking sector competition and intermediation efficiency in Kenya - Samuel Kiemo; Anne Kamau (Kenya Bankers Association (KBA), 2020)
This paper seeks to evaluate efficiency and competition dynamics of the Kenyan banking sector for the period 2001-2017 using bank-level data for 37 commercial banks. To achieve this, the paper uses a three-step estimation approach; first, we apply non-parametric Data Envelopment Analysis (DEA) to analyze measures of various aspects of efficiency in the banking sector; secondly, we apply Panzar-Rosse, H-statistics model to assess competition in the banking sector; thirdly we introduce the DEA efficiency scores as an explanatory variable in the re-estimated P-R equation to capture the role of efficiency in competition. The study findings indicate efficiency was on an upward trend and averaging at 69 percent. The results also indicate Kenyan-banking sector is characterized by monopolistic competition as shown by H-statistics of 0.59. Managerial ability measured by DEA efficiency score is found to be an important factor in promoting competition for the Kenyan banking sector. The study reveals there is room for Kenyan banks to improve on efficiency by optimizing on scale of operations, managerial abilities and continual adoption of technology. Further, bank consolidation over the years seems to favor efficiency and competition gains in the sector, therefore, authorities should continue adopting policies that promote greater banking sector efficiency and competition.
Keywords: 330; Competition; Efficiency; Banks; H-Statistics; Data Envelopment Analysis